2021
DOI: 10.1109/access.2021.3069379
|View full text |Cite
|
Sign up to set email alerts
|

Sampled-Data Resilient Control for Hybrid Nonlinear Stochastic Systems Under Periodic DoS Attacks

Abstract: This paper concerns the sampled-data resilient control for hybrid nonlinear stochastic systems under periodic denial of service (P-DoS) attacks. First of all, considering that the system is attacked by P-DoS and using the zero-order holder (ZOH) technique to further analyze the impact of such attacks on the control input. Secondly, via using the time-delay transform method, the attacked sampled-data resilient control system is modeled as a switched stochastic nonlinear time-delay closed-loop system. Thirdly, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We use the values of đ›Œ i , 𝜙 i , h, 𝜎, and đ›Ÿ in (43) and deal with the optimization problem for given distinct T: 25), subjects to LMIs (34), (38), and (39). (44) Table 1 gives the minimum values of T min off , the maximum allowable J ≜ (T − T min off )∕T × 100% called DoS attack rate, and 𝔏 2 − 𝔏 ∞ performance index đ›Ÿ. It can be observed that T min off , J, and đ›Ÿ increase with the increase of T in Table 1.…”
Section: Numerical Examplementioning
confidence: 99%
“…We use the values of đ›Œ i , 𝜙 i , h, 𝜎, and đ›Ÿ in (43) and deal with the optimization problem for given distinct T: 25), subjects to LMIs (34), (38), and (39). (44) Table 1 gives the minimum values of T min off , the maximum allowable J ≜ (T − T min off )∕T × 100% called DoS attack rate, and 𝔏 2 − 𝔏 ∞ performance index đ›Ÿ. It can be observed that T min off , J, and đ›Ÿ increase with the increase of T in Table 1.…”
Section: Numerical Examplementioning
confidence: 99%
“…In addition, pre-and post-multiplying ( 27) and ( 28) by X 12 and X 11 , respectively. Applying Schur Complement Lemma, we have (60) and (61) are equal to (27) and (28), respectively. By employing the similar approach, it is obvious that LMIs (29) and (30) tends to (62)-( 64) and (65), respectively.…”
Section: B Adaptive Event-triggered Extended Dissipative Control Designmentioning
confidence: 99%
“…Most of the published work addresses only one or two of these inherent attributes, while ignoring others [17], [18]. (2) Most of the existing results refer to periodic DoS attacks [20], [27], in the present study we deal with aperiodic DoS attacks, and the conditions developed for DoS duration and frequency are closer to the real situation. (3) The AETM is designed to actively balance the negative impact of aperiodic DoS attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Further considering that the gain in the controller will also be affected by uncertain factors and change, in the process of signal transmission between the factory and the controller, there are disturbances that will affect the gain of the controller, so the traditional control method will appear high vulnerability. The resilient control research based on the above uncertain system has stronger robustness and applicability, there have been some studies in this area 19‐23 . Chang et al 20 studies the state‐feedback resilient control problem for lateral motion regulation of an intelligent vehicle in the presence of randomly occurring uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al 20 studies the state‐feedback resilient control problem for lateral motion regulation of an intelligent vehicle in the presence of randomly occurring uncertainties. In Reference 21, the sampled‐data resilient control problem was solved for hybrid nonlinear stochastic systems under periodic DoS attacks.…”
Section: Introductionmentioning
confidence: 99%